Metode Pemahaman bagi Penelitian Antropologi - Ninuk Kleden (Antropologi Indonesia, 1999)
Amidst the many changes in the approaches taken by anthropologists today, the author re-examines the works produced in the more humanistic tradition of anthropology. She begins with the question of whether anthropological research can be conducted with an idiographic approach. Through a discussion of Verstehen, experience and hermeneutics, and drawing from her own experiences in the field, the author argues that the methods characteristic of a more humanistic anthropology can be applied to anthropological research and remain scientifically sound.